Pengaruh Ekspektasi Kinerja, Kepercayaan Auditor Pada Teknologi Informasi Dan Kompeksitas Bisnis Klien Terhadap Optimalisasi Penerapan TABK: ( Studi Empiris Pada Kantor Akuntan Publik Di DIY) - Septiana, Adinda Alita; Iswanaji, Chaidir; Nurcahya, Yulida Army (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to investigate the influence of performance expectations, auditor trust in technology, and client business complexity on the optimization of TABK application. This research is a quantitative descriptive study that aims to identify factors affecting the optimization of TABK application at Public Accounting Offices in Yogyakarta. The study uses primary data collected through questionnaires distributed to 18 Public Accounting Offices in Yogyakarta, measured using the Likert scale. The population of this study is public accounting auditors in Yogyakarta and the sampling technique used is purposive sampling. Based on the set criteria, 56 respondents were obtained. Data analysis was conducted using multiple linear regression analysis using SPSS version 25. The study found that performance expectations and client business complexity have a positive and significant influence on the optimization of computer-assisted audit techniques at Public Accounting Offices in Yogyakarta. Conversely, auditor trust in technology has a negative and non-significant influence on the optimization of computer-assisted audit techniques at Public Accounting Offices in Yogyakarta. Keywords: Performance Expectations; Auditor Trust; Client Business Complexity; Computer Assisted Audit Techniques.